3X-2Y)(X+Y)-X(3X-Y),其中X=2/3,Y=9/2 9(X-3)(X-2)-5(X-5)(2X-1)+3(X+1)(3X-4)其中X=-1/2

来源:学生作业帮助网 编辑:作业帮 时间:2024/05/09 21:01:34
3X-2Y)(X+Y)-X(3X-Y),其中X=2/3,Y=9/2 9(X-3)(X-2)-5(X-5)(2X-1)+3(X+1)(3X-4)其中X=-1/2

3X-2Y)(X+Y)-X(3X-Y),其中X=2/3,Y=9/2 9(X-3)(X-2)-5(X-5)(2X-1)+3(X+1)(3X-4)其中X=-1/2
3X-2Y)(X+Y)-X(3X-Y),其中X=2/3,Y=9/2
9(X-3)(X-2)-5(X-5)(2X-1)+3(X+1)(3X-4)其中X=-1/2

3X-2Y)(X+Y)-X(3X-Y),其中X=2/3,Y=9/2 9(X-3)(X-2)-5(X-5)(2X-1)+3(X+1)(3X-4)其中X=-1/2
1
(2-9)(2/3+9/2)-[3(2/3)^2+(2/3)(9/2)]
=-7*(31/6)-13/3
=-243/6
2
全部打开 原式=9x^2-45x+54-10x^2+55x-25+9x^2-3x-12
=8x^2+7x+17
=8*(1/4)+7(-1/2)+17
=31/2